Religion in Representations of Europe Shared and Contested Practices - Knauss, Stefanie; Pezzoli-Olgiati, Daria (Media and Religion | Medien und Religion, 2023)
"What is Europe exactly? How are ideas of Europe represented? What do we think of when we speak about religion in representations of Europe? And how does religion shape these conceptions? What are their effects? There is no single answer to these questions because there are too many different ideas of what Europe and religion should have been, are or need to be in the past, present and future respective-ly. This volume focuses on case studies in which ideas and concepts become crystallised: a text, a work of art, a building, an exhibition, a map, a film festival, a song or a meal. With contributions by Dolores Zoé Bertschinger, Carla Danani, Verena Marie Eberhardt, Natalie Fritz, Anna-Katharina Höpflinger, Ann Jeffers, Stefanie Knauss, Marie-Therese Mäder, Daria Pezzoli-Olgiati, Natasha O'Hear, Alexander Darius Ornella, Sean Michael Ryan, Alberto Saviello, Baldassare Scolari and Paola Wyss-Giacosa."